Pengaruh Profitabilitas terhadap Harga Saham Perusahaan Sektor Industri Barang dan Konsumsi di BEI Tahun 2017-2020 - Mohammad Rizqi Hisbullah (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
The stock price can measure effectiveness and company worth. This research aims to affect the company's ability to profit on the stock worth in the consumer goods industry. This research population is the consumer goods industry on The Indonesian Stock Exchange (IDX) from 2017-2020. The sample's selection method uses purposive sampling. Sampling criteria are companies listed on the Indonesia Stock Exchange in the industrial sector of goods and consumption that are not delisted and provide the information needed during 2017 to 2020, respectively. The number of data is one hundred and twenty (120). Data analysis use multiple linear regression by SPSS Statistics 26 for Mac from IBM. The effect of return on equity on stock price is significant positive”return on assets and net profit margin no significant effect on stock return. Companies need ROE to attract investors. The increase in ROE will affect the increase in stock prices.